Meta-analysis of normal reference values for right and left ventricular quantification by cardiovascular magnetic resonance - Zhan, Yang; Friedrich, Matthias; Dendukuri, Nandini; Lu, Yang; Chetrit, Michael; Schiller, Ian; Joseph, Lawrence; Shaw, Jaime L.; Chuang, Michael L.; Riffel, Johannes; Manning, Warren J.; Afilalo, Jonathan (Circulation. Cardiovascular imaging, 2024)
BACKGROUND: - Cardiovascular magnetic resonance (CMR) reference values are relied upon to accurately diagnose left ventricular (LV) and right ventricular (RV) pathologies. To date, reference values have been derived from modest sample sizes with limited patient diversity and attention to 1 but not both commonly used tracing techniques for papillary muscles and trabeculations. We sought to overcome these limitations by meta-analyzing normal reference values for CMR parameters stemming from multiple countries, vendors, analysts, and patient populations. - METHODS: - We comprehensively extracted published and unpublished data from studies reporting CMR parameters in healthy adults. A steady-state free-precession short-axis stack at 1.5T or 3T was used to trace either counting the papillary muscles and trabeculations in the LV volume or mass. We used a novel Bayesian hierarchical meta-analysis model to derive the pooled lower and upper reference values for each CMR parameter. Our model accounted for the expected differences between tracing techniques by including informative prior distributions from a large external data set. - RESULTS: - A total of 254 studies from 25 different countries were systematically reviewed, representing 12 812 healthy adults, of which 52 were meta-analyzed. For LV parameters counting papillary muscles and trabeculations in the LV volume, pooled normative reference ranges in men and women, respectively, were as follows: LV ejection fraction of 52% to 73% and 54% to 75%, LV end-diastolic volume index of 60 to 109 and 56 to 96 mL/m2, LV end-systolic volume index of 18 to 45 and 16 to 38 mL/m2, and LV mass index of 41 to 76 and 33 to 57 g/m2. For LV parameters counting papillary muscles and trabeculations in the LV mass, pooled normative reference ranges in men and women, respectively, were as follows: LV ejection fraction of 57% to 74% and 57% to 75%, LV end-diastolic volume index of 60 to 97 and 55 to 88 mL/m2, LV end-systolic volume index of 18 to 37 and 15 to 34 mL/m2, and LV mass index of 50 to 83 and 38 to 65 g/m2. For RV parameters, pooled normative reference ranges in men and women, respectively, were as follows: RV ejection fraction of 47% to 68% and 49% to 71%, RV end-diastolic volume index of 64 to 115 and 57 to 99 mL/m2, RV end-systolic volume index of 23 to 52 and 18 to 42 mL/m2, and RV mass index of 14 to 29 and 13 to 25 g/m2. - CONCLUSIONS: - Our Bayesian hierarchical meta-analysis provides normative reference values for CMR parameters of LV and RV size, systolic function, and mass, encompassing both tracing techniques across a diverse multinational sample of healthy men and women.
Online veröffentlicht: 20. Februar 2024
Gesehen am 07.02.2025